A revision of the unusual feather star genus Atopocrinus with a description of a new species (Echinodermata: Crinoidea) - Messing, Charles G. (Zootaxa, 2020)
Atopocrinus ojii new species, is described from deep water off Japan. The genus was previously monotypic and known only from the holotype of A. sibogae A. H. Clark, 1912, from Indonesia. Examination of all known specimens of Atopocrinus has added the following genus-level characters: cirrus sockets arising as tubes along the adoral surface of the centrodorsal, and faint, superficial, suture-like lines that cross the interradial ridges aboral to the centrodorsal/basal suture. The new species exhibits additional novel characters, some of which may be unique (e.g., deep pores around cirrus sockets) and others that may be shared with the incomplete holotype of A. sibogae (e.g., hollow pinnulars). Confusion about the structure of basal ossicles versus basal rays in Atopocrinus and other extant feather stars prompted inclusion of a review of the structure and development of these skeletal components. Video of a live specimen attributed to A. sibogae revealed that the distal half of the arms lack pinnules. The new species also shares several characters in common with Jurassic Spinimetra chesnieri Hess & Thuy, 2017.